EFL Students' Voices of Blended Collaborative Learning in Completing Digital Comic Projects - Utomo, Dias Tiara Putri; Ahsanah, Finaty; Ryandini, Elda Yulia (FKIP - Universitas Tanjungpura, 2024)
Advances in technology have made it possible to conduct collaborative learning online via the Internet. Blended collaborative learning combines online knowledge with on-site meetings to allow students to complete tasks and projects together in a group. This research aimed to elaborate voices of freshmen EFL students toward blended collaborative learning including perceived benefits, challenges, and how the students overcame the challenges, especially in completing digital comic projects. This phenomenological study was conducted at a private university in Indonesia. A total of 18 students participated in this study. They were interviewed face-to-face to obtain the data. The data were analyzed by qualitative data analysis by preparing the data, coding, and generating themes. The findings indicate the perceived benefits which included academic improvement, social and psychological benefits, and digital technology mastery. Additionally, challenges were found in terms of having different perceptions and ideas, lack of motivation and low responsibility to participate, and digital technology barriers. To tackle the problems, some efforts were made including building effective communication via collaborative tools, distributing various and equal roles, and learning from various sources.